Religiosity, Socio-Economics, and Entrepreneurial Spirit in the Global Muslim Community - Herianto; Nurhidaya; Ahmad, Amar; Jaman, Najma (El-Barka, 2025)
Entrepreneurship is one of the key drivers of prosperity and economic growth in a country. However, in the 21st century, Muslim entrepreneurs appear to lag behind their non-Muslim counterparts. According to Forbes World’s Billionaires List (2021), of the 1,826 global billionaires, the majority are non-Muslim entrepreneurs, while Muslim entrepreneurs are represented only at ranks 191 and 288. This study uses data from the World Bank and the World Values Survey (2010–2021), analyzed through a quantitative approach using a logistic regression model. The results show that among the six indicators of religiosity, only three dimensions have a significant influence on entrepreneurial spirit. Regarding socio-economic conditions, only marital status and income level demonstrate a significant positive effect on entrepreneurship among Muslim communities. The study concludes that married Muslims with higher income levels, who are diligent in prayer and strongly believe in the importance of God and religion in life, tend to have greater enthusiasm and motivation to engage in entrepreneurship. These findings are expected to serve as valuable input for both government and private stakeholders in formulating policies aimed at fostering entrepreneurship within Muslim societies.